Studies on the mechanism which prevents germination of unripe Triticale caryopses - Stanisław Weidner (Acta Societatis Botanicorum Poloniae, 2014)
Triticale (MT-3) caryopses were collected at three developmental stages (milk, milk-wax, and full ripeness i.e. 25, 39, 53 days after flowering) and germinated for 72 hours. The highest polyribosome contribution to the sum total of ribosomes, as well as, the highest 3H-uridine incorporation into the total ribosomal fraction of embryos (seedlings) were found at full ripeness, lower - at milk ripeness, and the lowest at milk-wax ripeness. Treatment of caryopses with gibberellin-A3 (GA3) and benzyloadenine (BA) caused an increase in the percentage of embryonic polyribosomes in caryopses which were collected at milk and full ripeness. Whereas the significant increase in 3H-uridine incorporation intothe total ribosomal fractions of embryos (seedlings) was observed only during the germination of the least ripe caryopses. This was characteristic of samples with caryopses at milk ripeness treated with BA, or BA and GA3 together. The studies proved that the mechanism which prevents the germination of unripe Triticale cyryopses and the formation of polyribosomes which were germination-induced, originated at the final stage of grain development, before its full ripeness.